Ecological Interaction Among Stingless Bees, Ants, and the whitefly Aleurothrixus aepim (Goeldi) - Alves, Luis Henrique; Pereira, Sérgio Nogueira; Prezoto, Fábio; Cassino, Paulo Cesar Rodrigues (EntomoBrasilis, 2015)
Many organisms consume honeydew to meet their energy requirements. Some species of stingless bees also consume honeydew secreted by hemipterans. In this study we describe the ecological relationships among stingless bees, ants, and the whitefly [Aleurothrixus aepim (Goeldi)]. In order to do so, we made 30-min observations twice a day, carried out once a week for four weeks in the month of April 2009, in a cassava plantation (Manihot esculenta Crantz) in Valença in the state of Rio de Janeiro, Brazil. Our results show no necessary dependence between the bees and A. aepim. The presence of ants help protect whiteflies from their natural enemies, A. aepim may be benefited by this interaction and thereby increase their evolutionary success. Interação Ecológica entre Abelhas sem Ferrão, Formigas, e a Mosca Branca Aleurothrixus aepim (Goeldi) Resumo. Muitos organismos consomem honeydew para suprir suas necessidades energéticas. Algumas espécies de abelhas sem ferrão, também utilizam este recurso com esta finalidade. Com o intuito de descrever a relação ecológica entre abelhas sem ferrão, formigas e mosca branca [Aleurothrixus aepim (Goeldi)], fizemos 30 minutos de observação 2 vezes ao dia, uma vez por semana, durante quatro semanas no mês de abril de 2009, em plantação de mandioca (Manihot esculenta Crantz), em Valença estado do Rio de Janeiro, Brasil. Não foi observada uma dependência obrigatória entre abelhas sem ferrão e A. aipim, caracterizando esta relação como comensal. Como a presença de formigas ajuda a proteger os aleirodídeos de seus inimigos naturais, A. aepim pode estar sendo beneficiado por esta interação e com isso, aumentando seu sucesso evolutivo.